The story of Eames furniture. - Neuhart, Marilyn, ....-; Neuhart, John, ....- (Berlin : Gestalten, 2010)
In this unique 2-volume, 800-page book with more than 2,500 images, Marilyn Neuhart tells the story, to paraphrase Charles Eames himself, of how Eames furniture got to be the way it is
Book 1: The early years - Book 2: The Herman Miller age